2021
DOI: 10.17671/gazibtd.780504
|View full text |Cite
|
Sign up to set email alerts
|

Performance Metrics and Monitoring Tools for Sustainable Network Management

Abstract: Network infrastructures comprise the backbone of our modern life, ranging in scale from relatively microlevel settings of offices or university campuses, to macro-level structures such as smart cities or national defense systems. Consequently, effective management of the quality and sustainability of provided services and network infrastructures has grown to be essential for modern service providers. Considering standard features like reliability, availability and maintainability, several questions are identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Chatterjee et al (2017) suggested technical, operational, social, and human factors to 5G network operation. Duman and Eliiyi (2021) identified the factors of sustainable network operation management as efficiency, service quality, capacity utilization, flexibility, availability, reliability, security, etc. Zhang and Gregory (2011) mentioned network structure, operations processes, governance system, support infrastructure, external relationships, etc., as critical success factors of global network operations.…”
Section: Ai Technology Adaptation In Network Operationsmentioning
confidence: 99%
“…Chatterjee et al (2017) suggested technical, operational, social, and human factors to 5G network operation. Duman and Eliiyi (2021) identified the factors of sustainable network operation management as efficiency, service quality, capacity utilization, flexibility, availability, reliability, security, etc. Zhang and Gregory (2011) mentioned network structure, operations processes, governance system, support infrastructure, external relationships, etc., as critical success factors of global network operations.…”
Section: Ai Technology Adaptation In Network Operationsmentioning
confidence: 99%
“…In India, targets are set for more than 90% repairs to be completed within one working day and 99% repairs in 3 days per Telecom Regulatory Authority of India (6). The Mean time to repair (MTTR) must be lower than the Mean time between failures (MTBF) for a network to perform well and is closely associated with reliability and availability of the network (7). Any delay in Fault repair will cost the service provider dearly, as customers' Quality of Experience (QOE) will deteriorate, and this leads to subscribers moving away from the current service provider.…”
Section: Fault Repair (>90% In 1 Working Day and >=99% In 3 Working D...mentioning
confidence: 99%
“…Duman & Eliiyi, 2021) Some important examples include uptime, response time, and packet loss and bandwidth usage.b. Response time:c. Packet loss: This happens when data packets traveling through a network don't make it to their destination(Lee et al, 2017).…”
mentioning
confidence: 99%